The aesthetics of calligraphy art in the Kiswah of the Kaaba / Duaa Mohammed Alashari - Alashari, Duaa Mohammed (Faculty of Art and Design, 2021)
Arabic calligraphy art is the main artistic element that has been used to ornament the Kiswah of the Kaaba. Beautiful examples of Arabic calligraphy composition and design can be found in the Kiswah of the Kaaba during the Saudi era. The Kiswah of the Kaaba is selected in the present research due to the unique composition of the Arabic calligraphy art. The study will provide a source of information to understand the Arabic calligraphy art applied to the Kiswah of the Kaaba from a unique perspective. This study is an artistic analysis to reveal about the aesthetics aspect of Arabic calligraphy design in the Kiswah of the Kaaba. The study utilised the qualitative method of research. The data collected for the study was analysed based on the Feldman's four-step approach in evaluating an artwork. The four steps are namely; descriptive, formal analysis, interpretation and judgment. The discussion section focuses on the detailed analysis of the artistic criticism method. The study concludes that the process of artistic criticism has led to reveal the aesthetics' element and principle of the Arabic calligraphy that is embodied within the applications of the Arabic calligraphy design in the Kiswah of the Kaaba. Also, the process of artistic criticism has led to reveal that the Kiswah of the Kabbah has achieved the highest aesthetical aspect of the Islamic art dimension.